Control of diapausing codling moth, Cydia pomonella (Lepidoptera: Tortricidae) in wooden fruit bins, using entomopathogenic nematodes (Heterorhabditidae and Steinernematidae). Issue 11 (1st November 2016) - Odendaal, Deidré; Addison, Matthew F.; Malan, Antoinette P.
ABSTRACT: Stacked wooden fruit bins are frequent overwintering sites for overwintering diapausing codling moth larvae. Control strategies against the codling moth ( Cydia pomonella ) (Lepidoptera: Tortricidae) in South Africa have been hampered by the reinfestation of orchards from nearby stacked infested fruit bins and by the movement of infested bins between orchards. Worldwide, wooden fruit bins are systematically being replaced with plastic bins, however in South Africa this will not be accomplished in the near future. The objective of this study was to evaluate the potential of two recycled commercially available entomopathogenic nematode (EPN) species, Heterorhabditis bacteriophora and Steinernema feltiae, as well as of a local species, Steinernema yirgalemense, to disinfest miniature wooden fruit bins under controlled conditions in the laboratory. After dipping miniature bins loaded with codling moth larvae in a suspension of 25 IJs/mL of each of the three EPN species, under optimum conditions of temperature and humidity, the highest percentage of control was obtained using S. feltiae (75%). The addition of adjuvants significantly increased S. feltiae infectivity to >95%, whereas it did not result in a significant increase in H. bacteriophora or S. yirgalemense infectivity.